2015
DOI: 10.1021/acs.oprd.5b00228
|View full text |Cite
|
Sign up to set email alerts
|

Development of Scalable Conditions for the Ugi Reaction—Application to the Synthesis of (R)-Lacosamide

Abstract: The Ugi reaction is applied for the preparation of (R)-lacosamide, an important drug for the treatment of epilepsy. To this end, key issues associated with the Ugi reaction, such as a practical preparation of the foul-smelling isocyanide as well as the efficient introduction of chirality via a cheap and easily removable chiral directing group were solved. Enantiomerically pure (>99.9% ee) drug substance meeting all required purity specifications is prepared in operationally simple four steps in 40% overall yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 35 publications
(20 reference statements)
0
26
0
1
Order By: Relevance
“…Although significant efforts have been made to purify the sample, strong lines of these contaminating species remain in the spectrum. The difficulties associated with the purity of methoxyacetaldehyde probably arise from its instability (Wehlan et al 2015) and the capability to form azeotropic mixtures with water and methanol (Brader & Johnson 1969).…”
Section: Methodsmentioning
confidence: 99%
“…Although significant efforts have been made to purify the sample, strong lines of these contaminating species remain in the spectrum. The difficulties associated with the purity of methoxyacetaldehyde probably arise from its instability (Wehlan et al 2015) and the capability to form azeotropic mixtures with water and methanol (Brader & Johnson 1969).…”
Section: Methodsmentioning
confidence: 99%
“…15 Isocyanide-based multicomponent reactions (IMCRs) is a highly relevant reaction classes and span a relevant chemical space in drug discovery as it enables easy discovery and/or access to multiple commercial and experimental drugs, e.g. anti-pain carfentanil and xylocaine, 16,17 antiseizure lacosamide, 18 anti-depressant olanzepine, 19 blood coagulation rivaroxaban and clopidogrel, 20,21 HCV drug telaprevir, 22 birth-controlling epelsiban, 23 or cancer-starvation ivosidenib, 24 just to mention a few. In particular IMCR is robust, scalable, safe, green and fulfils the important requirement for syntheses to tolerate nitrogen heteroatoms and (unprotected) polar functional groups common in drug molecules.…”
Section: Automation Is a Global Force That Will Transform Economies Amentioning
confidence: 99%
“…8 It has been repeatedly shown that by introducing a multicomponent reaction (MCR) into a target synthesis, the overall number of steps can be considerably reduced while yields are increased. [9][10][11] A perfect example is the Teleprevir HCV inhibitor synthesis by Orru et al 10 Introducing two MCR steps in the synthesis of this complex peptidomimetic compound reduced the lengthy >20 step industrial synthesis by ∼50%. Here we exemplary showcase the discovery and scope and limitation study of a new reaction leading to the small molecule quinazoline scaffold based on several major sustainability principles.…”
Section: Introductionmentioning
confidence: 99%